2020
DOI: 10.1016/j.injury.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Complications with focus on delirium during hospital stay related to femoral nerve block compared to conventional pain management among patients with hip fracture – A randomised controlled trial.

Abstract: Introduction: Patients with hip fracture often suffer complications leading to increased mortality and morbidity. Pain management are important, but opioids has many side effects. The aim of this study was to investigate whether Femoral Nerve Block (FNB) can reduce complications during hospital stay, with special focus on delirium compared to conventional pain management with opioids among patients with hip fracture, including those with dementia.Patients & Methods: In a randomized controlled trial involving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 43 publications
3
52
0
Order By: Relevance
“…However, it is hard for us to identify the relationship between them and POD for the lack of pre-operative records. The prevalence of POD varied from 10.5 to 42.0% in previous studies (25)(26)(27)(28)(29). The incidence of POD in this study was 19.3%, which is consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is hard for us to identify the relationship between them and POD for the lack of pre-operative records. The prevalence of POD varied from 10.5 to 42.0% in previous studies (25)(26)(27)(28)(29). The incidence of POD in this study was 19.3%, which is consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Chuan et al (2020) examined an analgesia bundle of care using femoral nerve blocks aimed at reducing multiple opioid use in particular intravenous morphine which showed reduced incidence of delirium in the intervention group. Unneby et al (2020) hypothesised that providing adequate analgesia via femoral nerve block may reduce the incidence of delirium. However, according to Unneby et al (2020) this protective factor may outweigh non‐modifiable risk factor of dementia.…”
Section: Resultsmentioning
confidence: 99%
“…Unneby et al (2020) hypothesised that providing adequate analgesia via femoral nerve block may reduce the incidence of delirium. However, according to Unneby et al (2020) this protective factor may outweigh non‐modifiable risk factor of dementia. No specific guides to pain management were provided in the reviewed articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study has a limitation of heterogeneity and lack of risk stratification. Unneby et al reported that femoral nerve block (FNB) did not reduce the incidence of postoperative delirium in patients with hip fracture [27]. They focused on patients with dementia, and a large proportion developed delirium (FNB group vs. placebo group: 50/52 vs. 55/57) regardless of FNB use.…”
Section: Incidence Of Deliriummentioning
confidence: 99%